Evaluation of the surface integrity characteristics of internal threads machined on lead-free brass alloy - KAYNAK, YUSUF (My University, 2023)
Tapping is a typical machining method being utilized in manufacturing internal threads. However, it contains few difficulties to be dealt with since during the process, many cutting edges involve synchronized axial and rotational movements. This work presents the results of an experimental study on the material type considering the influences of the manufacturing process (extrusion and forging) and tap type on the surface integrity characteristics of lead-free brass alloys. Experimental data on the surface quality of the threads, subsurface characteristics including microhardness is presented and analyzed. This study demonstrates that the manufacturing methods have a robust effect on microstructural aspects of low-lead brass alloy and resulting in hardening of the surface and subsurface.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Lead-Free Brass Alloy; Surface Integrity; Tapping; Threading